(untitled) (Baghdad Science Journal, 2009)
In situ hybridization assay was performed from 22 chronic hepatitis-C virus(CHC) patients (9 males and 13 females) (all of them known to be positive for anti-CH antibodies and high transaminase levels(GOT,GPT)) in order to study the necroinflammatory activity and detection of HCV-RNA in the sections of liver biopsies. The results showed that the percentage of infected cells were ranged from (10-100%) with mean value of 61.77%. The HCV-RNA was detected in the cytoplasm of hepatocytes.